Defining extent of sublobar resection: less may be more - Hennon, Mark; Yendamuri, Sai (Video-Assisted Thoracic Surgery; Vol 1 (November 2016): Video-Assisted Thoracic Surgery, 2016)
In this very interesting article, Altorki and colleagues address the very important question of whether sublobar resection with wedge resection for cT1N0 nonsmall cell lung carcinoma is equivalent to anatomic segmentectomy. Thoracic surgeons routinely face this dilemma when considering surgical resection in patients who are clearly not safe candidates for lobectomy, with the premise that segmentectomy is the “better” cancer operation (1).